Characterization of a group of specialized cardiomyocytes and their interaction with sympathetic neurons in murine heart - Duan, K (2019)
Our group recently described a distinctive, novel class of Pnmt+ cell-derived cardiomyocytes (PdCMs), with a potential endocrine role. However, our understanding of this new cardiomyocyte population is still very limited. There are numerous issues to be addressed such as the evidence of their endocrine machinery, their interaction with autonomic system, and their physiological function in the heart corresponding to their unique location in the heart. In order to address these issues, by using wild type and Pnmtcre/ChR2 mice as model systems, I have conducted a series of immunohistochemical and electrophysiological experiments with the aims of: i) exploring the potential endocrine machinery of PdCMs (Chapter 3); ii) clarifying their interaction with sympathetic neuron innervation (Chapter 4), and iii) determining their physiological role in the atria (Chapter 5). The key findings of this report include: i) firstly, a subtype of PdCMs containing vesicular structures was revealed by using immunostaining of vesicular monoamine transporter 2 (VMAT2) and myocyte marker α-actinin (aACT) as well as extra-neuronal monoamine transporter (EMT/ OCT3). This is the first time that such cellular vesicles have been found in cardiomyocytes. Although such vesicular structure requires further investigation, it opens a new frontier for exploring the cardiomyocyte endocrine function; ii) secondly, a synapse-like junction structure between these cardiomyocytes and sympathetic neuron innervation was identified by the staining of anti-Tyrosine Hydroxylase(TH) and anti-VMAT2; iii) finally, by using optogenetic stimulation combining with a high resolution optical imaging, the potential role as alternative pacemaker site of PdCMs was explored, which was induced by optogenetic pacing technique. In conclusion, the results presented in my report have provided novel evidence to suggest the endocrine function and the pivotal role in neurocardiac crosstalk of PdCMs.